2022
DOI: 10.3389/fpls.2022.957870
|View full text |Cite
|
Sign up to set email alerts
|

Combining spectral and wavelet texture features for unmanned aerial vehicles remote estimation of rice leaf area index

Abstract: Estimating the crop leaf area index (LAI) accurately is very critical in agricultural remote sensing, especially in monitoring crop growth and yield prediction. The development of unmanned aerial vehicles (UAVs) has been significant in recent years and has been extensively applied in agricultural remote sensing (RS). The vegetation index (VI), which reflects spectral information, is a commonly used RS method for estimating LAI. Texture features can reflect the differences in the canopy structure of rice at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…However, spectral information tends to saturate when vegetation canopy coverage is high and is easily affected by soil background reflectance in sparse plant areas. Additionally, previous research has shown that the texture information derived from UAV images can accurately predict winter wheat biomass [49,50]. Therefore, in this study, we introduced texture features based on vegetation indexes to construct an inversion model for comprehensive growth indicators of winter wheat that includes biomass.…”
Section: Combination Of Vis and Tfs As Input Variablesmentioning
confidence: 99%
“…However, spectral information tends to saturate when vegetation canopy coverage is high and is easily affected by soil background reflectance in sparse plant areas. Additionally, previous research has shown that the texture information derived from UAV images can accurately predict winter wheat biomass [49,50]. Therefore, in this study, we introduced texture features based on vegetation indexes to construct an inversion model for comprehensive growth indicators of winter wheat that includes biomass.…”
Section: Combination Of Vis and Tfs As Input Variablesmentioning
confidence: 99%
“…In contrast to the spectral reflectance that focuses on the crop's internal optical responses, texture features reflect the external morphological characteristics of the crop, offering rich spatial structure information on the crop canopy [20]. Therefore, the capability of texture features in capturing the dynamic changes in crop canopy growth makes it suitable for improving the precision of LAI estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous methods have been developed and provide promising LAI estimation results for rice [20,26], potato [28,29], maize [30,31], and other crops by combining both VI and TF to date, it is still remarkably challenging due to the following aspects. First, despite the combination of both, VI and TF have been demonstrated to have important value for monitoring LAIs of multiple crops; as far as we are aware, fewer studies specifically address the effect of both vegetation indices and texture features on the peanut LAI estimation since differences in the canopy structures of different crops might lead to changes in texture characteristics as well as spectral absorption and reflection characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this study aimed to investigate the potential of quantifying lodging scores of soybean breeding lines using UAV-based imagery and machine learning methods. The textural image features provide Supplementary Information about the object properties, which can help the heterogeneous crop field assessment [ 45 ]. The specific objectives were: (1) to develop an RGB image texture feature-based soybean lodging classification model using machine learning algorithms and (2) to assess the classification accuracies among different classification models.…”
Section: Introductionmentioning
confidence: 99%